PENINGKATAN HASIL BELAJAR TOLAK PELURU GAYA MENYAMPING MELALUI PENDEKATAN BERMAIN PADA SDN 05 SETABAR - Hendrikus, Hendrikus; Simanjuntak, Victor Gaperius; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is how to improve the learning outcomes of bypass style by using play approach on the students of class VI SDN 05 Setabar Landak District ?. The purpose of this research is to improve the learning outcomes by using a play approach. This research uses classroom action research which is the basis for improving the learning that will be produced, with the following steps: 1) Planning, 2) implementation, 3) observation, 4) reflection; Subjects used as many as 28 students. Data were collected by questionnaire / questionnaire and test each cycle. From the results of the research In the preliminary test before the action was seen that the learning value of the sideways force tossing force averaged 64th grade and the number of percentage of classical completeness only reached 25%. In the first cycle action using the play approach can improve learning sideways stylistic departure force obtained average learning outcome 74 with 64% classical mastery. In the second cycle action by using the play approach can improve learning sideways stylistic departure force obtained average learning outcome 77 with classical completeness increased by 96% and observation value of student activity getting better.Â Keywords: Learning, Reject Bullets, Play Approach.Â